Nulidades no processo civil - Carvalho, Paula Gomes (2014)
This dissertation focused on analyzing the invalidities, which may occur on the field of Civil Procedural Law, firstly with the studies of the dimensions of existence, validity and effectiveness of the legal universe, as imagined for the general theory of law. However, about this same base, there is no way of fully transferring the concept of invalidities from substantive to procedural law, taking into consideration its distinctiveness. The declaration of nullity, on the scope of procedure, is considered by the tenet as a true form of sanction. In fact, the entire system of invalidation has been created to avoid the declaration of nullity, by preserving the acts that have not been damaged, in an attempt of “saving” the procedure. All this due to the principles which guide this subject, observed in the Code of Civil Procedure. Thus, considering the various types of defects, which may taint the procedure, it is necessary to identify its characteristics in order to investigate its effects on the concrete case, in other words, if it will or will not be materially altered. Subsequently, we tried to examine the methods used to raise nullity and require its invalidation, as well as the question of possible remediation of flaws. Finally, through detailed theoretical studies, enclosing legislation and doctrinaire beliefs, we intend to enlighten the differentiated treatment granted to the nullities in the procedure, concluding that, on the contrary to what happens in Civil Law, they are generally prone to validation